Isolation improvement of SPDT discrete switch with single switchable open stub resonator at 2 GHz band - Shairi , N. A (IEEE, 2012)
Generally, if using single low performance discrete PIN diode, it is difficult to get high isolation of Single Pole Double Throw (SPDT) switch at 2 GHz band. The PIN diodes are usually packaged in a standard package such as SOT23, SOT323, SOD323 or SOD523. Therefore, this paper proposed single switchable open stub resonator for isolation improvement of shunt SPDT discrete PIN diode switch for Time Division Duplex switching of wireless communication system at 2 GHz band. The discussion of the conceptual and operation of the resonator are included in this paper. The circuit has been simulated for further analysis in simulation software where parameters of microstrip line and FR4 substrate have been taken into account. Result in simulation has shown high isolation between 25 to 28 dB at frequency of 2 to 3 GHz compared to conventional shunt SPDT switch and has been verified with measurement.